20,000 Leagues Under the Sea: The Classic Story, Plus Fascinating Background Facts And Photographs - Jules Verne & Paul Wright; D.K. Publishing
A nineteenth-century science fiction tale of an electric submarine, its eccentric captain, and undersea world, which anticipated many of the scientific achievements of the twentieth century.